2019
DOI: 10.2174/1570161116666180709095348
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal Hormone Therapy and Cardiovascular Risk: Where are we Now?

Abstract: Transition to menopause is associated with an increase in cardiovascular disease (CVD) risk, mainly attributed to lipid and glucose metabolism dysregulation, as well as to body fat redistribution, leading to abdominal obesity. Indeed, epidemiological evidence suggests that both early menopause (EM, defined as age at menopause <45 years) and premature ovarian insufficiency (POI, defined as age at menopause <40 years) are associated with 1.5-2-fold increase in CVD risk. Menopausal hormone therapy (MHT) exerts a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 83 publications
0
34
0
6
Order By: Relevance
“…Depression is more frequently observed in women, and menopause is a critical predisposing factor for the psychiatric disorders. Although estrogen replacement therapy is reported effective on the mental disorder progression, there is a great concern of the side-effects of chronic estrogen treatment, such as breast cancer and cardiovascular events [20,21]. Therefore, it becomes urgent to explore the underlying mechanisms of menopause-related depression and seek an alternative treatment strategy for the mental condition.…”
Section: Discussionmentioning
confidence: 99%
“…Depression is more frequently observed in women, and menopause is a critical predisposing factor for the psychiatric disorders. Although estrogen replacement therapy is reported effective on the mental disorder progression, there is a great concern of the side-effects of chronic estrogen treatment, such as breast cancer and cardiovascular events [20,21]. Therefore, it becomes urgent to explore the underlying mechanisms of menopause-related depression and seek an alternative treatment strategy for the mental condition.…”
Section: Discussionmentioning
confidence: 99%
“…Despite existing side effects, estrogen supplementation is still the main method for treating perimenopausal syndrome. 32,33 Perimenopausal supplementation of estrogen can improve lipid metabolism 34 and inhibit AS progression [35][36][37] . We found that estrogen supplementation restored the serum lipid levels of ovariectomized ApoE −/mice to those of ApoE −/mice without receiving ovariectomy even after HFD feeding, suggesting that estrogen had a great influence on the lipid metabolism in females.…”
Section: Discussionmentioning
confidence: 99%
“…e increase in cardiovascular diseases following the onset of menopause has proved that estrogen is a cardiovascular protective agent [18,19]. However, estrogen replacement therapy was reported to be related to a higher rate of endometrial cancer, breast cancer, and thromboembolic events [20]. erefore, it is important to search for a safe and effective selective regulator of ER in natural products.…”
Section: Evidence-based Complementary and Alternative Medicinementioning
confidence: 99%